Інформаційна технологія створення ботів-експертів на основі процедуральних знань - Тімофєєв, Володимир Олександрович; Гуца, Олег Миколайович; Пересада, Олена Василівна (НТУ "ХПІ", 2017)
Відмінності у формах представлення знань не дають можливості застосовувати існуючі інформаційні технології створення чат-ботів (використовують декларативні знання) задля поширення через інтернет процедуральних знань у вигляді ботів-експертів. Запропоновано оригінальну інформаційну технологію, що дозволяє вирішити цю проблему. Матеріал адресований ІТ-фахівцям, експертам в різних областях та керівникам підприємств задля використання при створенні консалтингового інтернет-бізнесу або задля вирішення організаційних проблем в існуючому бізнесі.

Now the world web answers the questions "who?", "what?", "where?" and "when?" fast and completely. But not the question "how?", especially "how to settle emergency situation?" (which refers to procedural knowledge) usually private user's advices from various forums are employed as response. And this is despite the real boom of bots-programs that mimic human action through the Internet interfaces and of the so-called chatbots, that are the programs to provide answers within individual sites. The differences in knowledge representation forms make it impossible to use existing chatbot creation information technologies for dissemination the procedural knowledge in bot-experts form via Internet. For the problem solution, the original information technology is offered. The article is addressed to IT-specialists, experts in various areas and to heads of the enterprises to use for creating of the Internet consulting business or to solve of organizational problems in an existing business.
The Bots Experts based on the procedural knowledge creation Information Technology
Keywords: бот; декларативне знання; експертна система; інформаційна технологія; процедуральне знання; bot; declarative knowledge; expert system; information technology; procedural knowledge